Perancangan Sistem Informasi Pencatatan dan Pemberitahuan Pembayaran Sumbangan Pembinaan Pendidikan (SPP) pada SMP Swasta Muhammadiyah Plus Bengkalis - Amalia, Suci; Yasnita, Zhafiratunnisa’; Rahmayani , Mentari Tri Indah (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
The information system for paying educational contribution at SMPS Muhammadiyah Plus Bengkalis still uses a manual system. This design aims to develop the technology used today, such as designing an information system for recording and notification of paying educational contribution at SMPS Muhammadiyah Plus Bengkalis. Payment for Education Development Contributions (SPP) still often experiences problems such as data collection and processing of payment information which is still done manually through ledgers so that it takes a lot of time and effort in searching student data. In designing this information system using the SDLC method which functions to develop and design high quality software. This information system uses the Java programming language.